De vidas e vínculos: as lutas dos motoristas plataformizados por reconhecimento, redistribuição e representação no Brasil - Ana Carolina Reis Paes Leme (2022)
The present research has as its theme the struggle for access to justice through the rights of workers platformed for recognition, redistribution and representation, from the perspective of Nancy Fraser's three-dimensional theory. The objective is to present and critically debate the multiplicity of blocks, of different natures, to the access to justice of these drivers platformed by the way of Rights. The theoretical framework is the conceptions of access to justice through the Rights of Marona, Avritzer and Gomes and of three-dimensional justice by Nancy Fraser. The methodology was structured on two axes: bibliographic research and semi-structured interviews. The research developed in this thesis is exploratory-descriptive, describing a social phenomenon. The method was to carry out in-depth interviews. To answer the elaborated questions, this research was anchored in a central approach of the qualitative type. From the interviews, it was possible to analyze the creation of four distinct categories, in order to present the results: 1) working conditions; 2) collective organization; 3) demands for dialogue; and 4) access to justice. In order to guide the critical debate on the multiple obstacles to access to justice through Rights, in the light of Fraser's three-dimensional conception, the analysis was again divided around the following axes: 1) the indivisibility of the categories, redistribution, recognition and representation; 2) from gender to recognition as a person; 3) the defensive speech regarding the employment relationship and the understanding in extension of the legal relationship in its protections and limits; and 4) judicial decisions and the activation/demobilization of the union movement. After the indication of these divisions, considerations will be made about the dimension of criticism of the employment relationship, pointing out what the empirical has to say to the positive normativity, in addition to the normatized labor rights: it is necessary to go beyond the employment relationship and access the recognition of being seen as social subjects, deserving of dignity in terms of social value, not being exposed to harassment and discrimination in different ways and they demand for forums for debates and discussion of working conditions by the parties involved, in parity of participation.